Social Sport Club and Youth Sport Expectations: Personal and Social Determinants in Contrasting Ecologies of Practice - Domingues, Márcio Luis Pinto; Gonçalves, Carlos Eduardo (American Journal of Human Ecology, 2012)
This study aimed at determining how environmental practices and significant others alongside operate in shaping sport experiences. Recent research brought evidences that different ecologies of practice produce different personal outcomes for the athletes who engage in competitive settings for long periods of time. The purpose of the study was to explore how significant others perceive football sport environment in an economically and socially underserved milieu, to clarify the effects of sport engagement and to highlight the factors that can optimize the positive influences associated with sport participation. Field diary, document analysis and semi-structured interviews were conducted to 12 significant others with an active role in the club, participant observation along with field diary were also completed during this longitudinal study in the 2010/2011 sport season. Significant others displayed an unexpected sense of community in the social club and they perceive as being strong influences on athlete’s perceptions of the environment and motivation exerted. Despite the conditions, adults in social clubs see sport as having an important social positive role justifying overall convictions about the importance of sport practice for underserved youth and the more profound study of reality in these environments.